2022
DOI: 10.3390/microorganisms10101996
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 S1 Spike Protein Promotes MAPK and NF-kB Activation in Human Lung Cells and Inflammatory Cytokine Production in Human Lung and Intestinal Epithelial Cells

Abstract: The coronavirus disease 2019 (COVID-19) pandemic began in January 2020 in Wuhan, China, with a new coronavirus designated SARS-CoV-2. The principal cause of death from COVID-19 disease quickly emerged as acute respiratory distress syndrome (ARDS). A key ARDS pathogenic mechanism is the “Cytokine Storm”, which is a dramatic increase in inflammatory cytokines in the blood. In the last two years of the pandemic, a new pathology has emerged in some COVID-19 survivors, in which a variety of long-term symptoms occur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 84 publications
2
26
0
Order By: Relevance
“…Most studies of SARS-CoV-2 structural proteins have been conducted in vitro using an array of human and mouse cells. Both the S protein or it’s S1 subunit is sufficient to elicit a proinflammatory immune response in primary cells and cell lines including human lung cells ( Forsyth et al, 2022 , Khan et al, 2021 , Patra et al, 2020 ), human endothelial cells ( Perico et al, 2022 ), human intestinal epithelial cells ( Forsyth et al, 2022 ), HL-60 cells ( Zhao et al, 2021 ), human monocytes/macrophages ( Karwaciak et al, 2021 , Khan et al, 2021 , Pantazi et al, 2021 , Schroeder and Bieneman, 2022 , Shirato and Kizaki, 2021 , Zhao et al, 2021 ), mouse macrophages ( Li et al, 2022 , Shirato and Kizaki, 2021 , Zhao et al, 2021 ), human peripheral blood mononuclear cells ( Olajide et al, 2021b ), and TF1PIGA null cells ( Yu et al, 2020 ). Interestingly, Zhao and colleagues examined the proinflammatory effects of different domains of the S protein and found that the N-terminal (NT) and receptor binding (RB) domains (D) failed to elicit a proinflammatory cytokine response.…”
Section: Sars-cov-2 Glycoproteins Function As Pampsmentioning
confidence: 99%
“…Most studies of SARS-CoV-2 structural proteins have been conducted in vitro using an array of human and mouse cells. Both the S protein or it’s S1 subunit is sufficient to elicit a proinflammatory immune response in primary cells and cell lines including human lung cells ( Forsyth et al, 2022 , Khan et al, 2021 , Patra et al, 2020 ), human endothelial cells ( Perico et al, 2022 ), human intestinal epithelial cells ( Forsyth et al, 2022 ), HL-60 cells ( Zhao et al, 2021 ), human monocytes/macrophages ( Karwaciak et al, 2021 , Khan et al, 2021 , Pantazi et al, 2021 , Schroeder and Bieneman, 2022 , Shirato and Kizaki, 2021 , Zhao et al, 2021 ), mouse macrophages ( Li et al, 2022 , Shirato and Kizaki, 2021 , Zhao et al, 2021 ), human peripheral blood mononuclear cells ( Olajide et al, 2021b ), and TF1PIGA null cells ( Yu et al, 2020 ). Interestingly, Zhao and colleagues examined the proinflammatory effects of different domains of the S protein and found that the N-terminal (NT) and receptor binding (RB) domains (D) failed to elicit a proinflammatory cytokine response.…”
Section: Sars-cov-2 Glycoproteins Function As Pampsmentioning
confidence: 99%
“…S1 spike protein might be not only responsible for the adherence and the invasion of the virus to the host cells and the onset of the cytokine storm but also responsible for long-COVID syndrome [ 23 ]. Moreover, it was estimated that a greater number of free S1 spikes in the blood during COVID-19 infection is correlated with a poor prognosis of COVID-19 [ 24 ]. Fortunately, the huge number of the accumulated mutation in the spike protein of the latest variants of concern results in a disrupted recognition of certain Toll-like receptors (TLR), resulting in the lower activation of the NF-κB pathway and related signaling pathways [ 25 ].…”
Section: Immune Response and Circulating Extracellular Vesicles Conta...mentioning
confidence: 99%
“…There is reason to believe that vaccines encoding the spike (S) protein of SARS-CoV-2 have additional mechanisms of harm, owing to the biological impacts of S protein specifically. There is a wide literature [150][151][152][153], and it is beyond the scope of this review to cover this in significant depth. However, the addition of spike protein adds another factor in assessing the complexity of RNA vaccines.…”
Section: Harms Of Rna Vaccination With Sars-cov-2 Spike (S) Antigenmentioning
confidence: 99%